Issues related to education in the periodical scientific production of the research productivity scholars in the area of information science in Brazil - Bufrem, Leilah Santiago; Tannuri de Oliveira, Ely Francina [UNESP]; Sobral, Natanael Vitor; Alves, Bruno Henrique (Biblioteca Nacl Cuba Jose Marti, 2018)
Objective. To analyze issues related to Education in the scientific production of Information Science, derived from articles of Information Science researchers in Brapci between the years 1972 and 2015. Design/Methodology/Approach. The bibliometric procedures and their production and citation indicators were used. A database was constructed from the scientific production of 47 researchers. Articles were retrieved by using the following search terms: education, teaching, learning and curriculum. Vantage Point (R), Microsoft Excel (R), UCINET (R) and Netdraw (R) were employed as data processing and analysis tools. Results/Discussion. The major themes were related to Library and Library Science; Technology; Information Literacy; Archives and Archives; Universities and Distance Education. It brings the most cited authors and the most intense relationships between cited authors and keywords. Conclusions. The most cited authors turn to studies on information policies, literacy, ethical issues and information communication. Originality/Value. The study is sustained by the need to clarify the interdisciplinary and inter-domains relations between Information Science and Education.
Keywords: Education; Information Science; Scientific Production; Researchers in Productivity (Information Science); Brapci